Accelerometer-derived physical activity and sedentary time and cardiac biomarkers: The Maastricht Study - Vandercappellen, E. J.; Koster, A.; Savelberg, H. H. C. M.; Eussen, S. J. P. M.; Dagnelie, P. C.; Schram, M. T.; van Greevenbroek, M. M. J.; Wesselius, A.; Kooman, J. P.; Kroon, A. A.; Henry, R. M. A.; Stehouwer, C. D. A. (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac troponins and NT-proBNP are biomarkers of cardiac injury that are used clinically in the diagnosis of myocardial infarction and heart failure. It is not known whether the amount, types and patterns of physical activity (PA) and sedentary behaviour are associated with levels of cardiac biomarkers. Methods In the population-based Maastricht Study (n=2370, 51.3% male, 28.3% T2D) we determined cardiac biomarkers hs-cTnI, hs-cTnT, and NT-proBNP. PA and sedentary time were measured by activPAL and divided into quartiles (quartile 1 (Q1) served as reference). The weekly pattern of moderate-to-vigorous PA (insufficiently active; regularly actives; weekend warriors) and coefficient of variation (CV) was calculated. Linear regression analyses were conducted with adjustment for demographic, lifestyle, and cardiovascular risk factors. Results There was no consistent pattern between physical activity (different intensities: total, light, moderate-to-vigorous and vigorous) and sedentary time on the one hand and hs-cTnI and hs-cTnT on the other. Those with the highest levels of vigorous intensity PA had significantly lower levels of NT-proBNP. With regard to PA patterns, weekend warriors and regularly actives had lower levels of NT-proBNP but not with hs-cTnI and hs-cTnT (reference:insufficiently actives). A higher weekly moderate-to-vigorous PA CV (indicating more irregular activity) was associated with lower levels of hs-cTnI and higher levels of NT-proBNP, but not with hs-cTnT. Conclusions In general, there was no consistent association between PA and sedentary time and cardiac troponins. In contrast, vigorous and possibly moderate-to-vigorous intensity PA, especially if done regularly, was associated with lower levels of NT-proBNP.